Resource Assessment of Limestone Based on Engineering and Petrographic Analysis - Hussain, Javid; Zhang, Jiaming; Lina, Xiao; Hussain, Khaleel; Shah, Syed Yasir Ali; Ali, Sajid; Hussain, Altaf (Salehan Institute of Higher Education, 2022)
The China-Pakistan Economic Corridor (CPEC) is a massive in-progress construction project in Pakistan that connects more than 70 countries via multiple trade channels such as highways, railways, roads, and fiber optics. This project also involves the development of local infrastructure and industrial zones in Pakistan, which demands the discovery of new resources of aggregate to facilitate the construction. Therefore, physical characterization research was carried out on the Kirman hill region (Jurassic limestone), District Kurram, Pakistan, to investigate their suitability for utilization as construction materials using site investigation and laboratory studies. The results outline that all typical engineering parameters are within acceptable limits set by international standards like BS, ASTM, and AASHTO. Bituminous tests revealed that Jurassic limestone is appropriate as an aggregate for asphalt wearing coarse. Likewise, the petrographic study performed shows proper matching with engineering tests. The petrographic analysis of Jurassic limestone showed a minute amount of deleterious content; as a result, it is resistant to Alkali silica reaction (ASR) and Alkali carbonate reaction (ACR) expansions. Based on engineering and petrographic analysis, the Jurassic limestone, Kirman hill region, District Kurram, Pakistan is recommended as a potential aggregate for (i.e., base course, subbase course, cement concrete, and asphalt) and other mega and minor civil construction projects.Â Doi: 10.28991/CEJ-2022-08-03-02 Full Text: PDF